POLITICS OF SPORT IN THE AGE VARGAS (Fiep Bulletin - online, 2014)
The objective of this article is to carry through an analysis of the relations that if had established between the sports sphere and the State in a specific period of the history of Brazil: the Age Vargas (1930-1945). In Brazil, the governmental actions that had objectified prescribed, to command and to control of direct form the sports sector had occurred after this having reached a great institutional development in the scope of the private relations. From years 1930 it had a change in the standard of intervention of the State in the society and, in special, the totalitarian sports sector characterized by, being centered, bureaucratic and corporatist. In this period, the sport was used to organize the space and the time of the workers, to inculcate wrong ideological values to its interests of classroom, to produce and to reproduce one definitive force of made use work to be explored in favor of the capital.